2006
DOI: 10.1189/jlb.0306219
|View full text |Cite
|
Sign up to set email alerts
|

Differential infection of mononuclear phagocytes by Francisella tularensis: role of the macrophage mannose receptor

Abstract: Francisella tularensis (Ft) is a Gram-negative bacterium and the causative agent of tularemia. It is well established that this organism replicates inside macrophages, but we are only beginning to understand this interface at the molecular level. Herein, we compared directly the ability of Ft subspecies holarctica live-vaccine strain to infect freshly isolated human peripheral blood monocytes, monocyte-derived macrophages (MDM), and cells of the murine macrophage cell line J774A.1 (J774). We now show that unop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
176
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(185 citation statements)
references
References 59 publications
6
176
2
1
Order By: Relevance
“…than by colony count, may have contributed to these findings. Other studies, which have found less efficient entry into macrophages by the F. tularensis subspecies holarctica vaccine strain (8,9), also did not use the particular army lot 11 strain used herein, or the derivation of the strain was not detailed (39). Metabolic studies of various lots of the Francisella vaccine strain (Ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…than by colony count, may have contributed to these findings. Other studies, which have found less efficient entry into macrophages by the F. tularensis subspecies holarctica vaccine strain (8,9), also did not use the particular army lot 11 strain used herein, or the derivation of the strain was not detailed (39). Metabolic studies of various lots of the Francisella vaccine strain (Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplicities of infection (MOI) Ͼ10 -60 were required to achieve efficient infection. A role for the mannose receptor was further confirmed in an infection model using F. tularensis LVS and J774 macrophages, where induction of expression of the mannose receptor on human monocyte-derived macrophages by IL-4 led to a significant increase in the uptake of Francisella (9). The authors also acknowledged that because neither blockage of the mannose receptor nor of the complement receptor could ablate infection, there are probably more receptors involved.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Thereafter, the cells were washed twice in PBS to remove any unbound material, and MDDC were allowed to adhere to an eight-chamber microscopy slide for 20 min. Adherent MDDCs were washed in PBS, fixed in 10% formalin for 15 min at 25°C, and then permeabilized in 50% methanol/50% acetone for 5 min at 4°C as previously described (31). Fixed and permeabilized cells were rinsed in PBS supplemented with 0.5 g/L sodium azide and 5 g/L BSA, and then blocked in PBS containing 10% heat-inactivated normal horse serum (blocking buffer) for 1 h at 25°C (31).…”
Section: Immunofluorescence Microscopy and Image Processingmentioning
confidence: 99%
“…The antibodies, OX-42, and Mac-1 that recognize CD11b generally used to detect microglia in rat and mouse, respectively, are unable to distinguish among microglia, neutrophils, and monocytes, since CD11b is expressed in all three cell types (Akiyama and McGeer, 1990;Jones et al, 1988;Schulert and Allen, 2006). In this study, we examined the behavior of these inflammatory cells in lipopolysaccharide (LPS)-injected brain using the additional markers, myeloperoxidase (MPO), and ionized calcium binding adaptor molecule-1 (Iba-1).…”
Section: Introductionmentioning
confidence: 99%